Cognitive bias modification in problem and pathological gambling using a web-based approach-avoidance task: A pilot trial. (February 2019) - Wittekind, Charlotte E.; Bierbrodt, Julia; Lüdecke, Daniel; Feist, Ansgar; Hand, Iver; Moritz, Steffen
Highlights : First study adopting the AAT for training purposes in gambling. Study was set up as a web-based training. Both groups showed a significant reduction of gambling-related symptoms. Study holds valuable information for larger trials in the future. Abstract: There is evidence that training addicted participants to implicitly avoid disorder-related stimuli by using a training version of the Approach-Avoidance Task (AAT) results in reduced substance consumption (i.e., Approach Bias Modification [AppBM]). The aim of the present web-based study was to investigate the feasibility and effectiveness of AppBM in reducing gambling-related symptoms. A self-selected sample of participants with problem/pathological slot-machine gambling completed an online survey and received either AppBM or Sham training (final N  = 131). Attrition during study participation was high (66%). In both conditions slot-machine related and neutral pictures were presented. Within the AppBM condition all slot-machine related pictures had to be pushed and all neutral pictures had to be pulled, whereas in the Sham condition the contingency was 50:50. Eight weeks after baseline, participants were re-assessed. Both groups showed a similar reduction in gambling-related symptoms. Findings are at odds with the hypothesis claiming that only contingency trainings yield beneficial effects. However, it cannot be ruled out that effects result from other factors unrelated to training such as expectancy effects. We think this study holds valuable information how to conduct larger trials in the future and may prove helpful to improve training and its delivery.